Hypertrophy of the Inferior Olivary Nucleus Impacts Perception of Gravity - Tarnutzer, Alexander A.; Palla, Antonella; Marti, Sarah; Schuknecht, Bernhard; Straumann, Dominik (Frontiers in Neurology, 2012)
Interruption of the Guillain-Mollaret triangle interconnecting the red nucleus, the inferior olivary nucleus and the contralateral dentate nucleus is predicted to interfere with the dentate nucleus’ role in estimating direction of gravity. In a patient with pendular nystagmus due to hypertrophic inferior olivary nucleus degeneration secondary to ponto-mesencephalic hemorrhage, perceived vertical shifted from clockwise to counter-clockwise deviations within 4 months. We hypothesize that synchronized oscillations of inferior olivary nucleus neurons induce a loss of inhibitory control, leading to hyperactivity of the contralateral dentate nucleus and, as a result, to perceived vertical roll-tilt to the side of the overactive dentate nucleus.